OSTEOPOROSIS SCREENING TECHNOLOGY APPLICATION TO IMPROVE HEALTHY LIFESTYLES OF SCHOOL RESIDENTS IN PORONG, SIDOARJO - Lailatul Muqmiroh; Amillia Kartika Sari; Berliana Devianti Putri; Muhaimin Muhaimin (Darmabakti Cendekia: Journal of Community Service and Engagements, 2022)
Background : Osteoporosis is one of degenerative disease that can affect elderly and children as well. Knowledge about Osteoporosis has not been fully understood by school residents and their community.  Objectives : This activity aims to (1) increase the school residents knowledge about Osteoporosis, (2) provide digital health communication media that can be used widely and easily by school residents, (3) increase the ability of school residents to use osteoporosis screening technology application and disseminate to the community. Method : Training and mentoring using ATOs-A application media and pocket books. Monitoring and evaluation is carried out to see and assist teachers in using the Osteoporosis screening application. Knowledge improvement is measured by pre-post test using questionnaire as a tool. Result : There is improvement of school residents knowledge about Osteoporosis and how to use screening technology application. So that, they have more encouragement to improve their knowledge and propagate it to community. Conclusion : Community service has a positive response from school residents and benefits to improve the healthy lifestyle in that area.